2021
DOI: 10.1101/2021.10.28.21263107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiplex PCR Assays for Identifying All Major SARS-CoV-2 Variants

Abstract: Variants of Concern (VOC) of SARS-CoV-2, including Alpha, Beta, Gamma, and Delta, threaten to prolong the pandemic leading to more global morbidity and mortality. Genome sequencing is the mainstay of tracking the development and evolution of the virus, but is costly, slow, and not easily accessible. A multiplex qRT-PCR assay for SARS-CoV-2 was developed, which identifies all VOC as well as other mutations of interest in the viral genome, eight mutations total, using single nucleotide discriminating molecular b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Because variations propagate throughout populations over time, these techniques may allow for an improved search of variants, particularly in resource-limited contexts. 62,63 Genome sequencing is the gold standard for tracking the virus's genesis and evolution, but it is expensive, time-consuming and challenging to get.…”
Section: Ngs Sequencing Methods Have Quickly Established Themselves A...mentioning
confidence: 99%
See 2 more Smart Citations
“…Because variations propagate throughout populations over time, these techniques may allow for an improved search of variants, particularly in resource-limited contexts. 62,63 Genome sequencing is the gold standard for tracking the virus's genesis and evolution, but it is expensive, time-consuming and challenging to get.…”
Section: Ngs Sequencing Methods Have Quickly Established Themselves A...mentioning
confidence: 99%
“…Although PCR techniques target preselected mutations, they are less expensive and more convenient than sequencing for SARS‐CoV‐2 genotyping, producing more rapid results. Because variations propagate throughout populations over time, these techniques may allow for an improved search of variants, particularly in resource‐limited contexts 62,63 . Genome sequencing is the gold standard for tracking the virus’s genesis and evolution, but it is expensive, time‐consuming and challenging to get.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…56,57 For VOCs, including the Omicron variant, two-tube multiplex qRT-PCR can detect five copies of viral RNA. 58 Next-generation sequencing has become the gold standard for identifying Omicron. Scott et al 59 have shown that viral genome sequencing can be used for detecting apparent deletions of the S gene (S-).…”
Section: Detection Of Omicron Variantmentioning
confidence: 99%
“…In addition, RT‐PCR testing is necessary for potentially infected individuals with Omicron, such as a history of recent travel to the epidemic area and close contact with confirmed patients 56,57 . For VOCs, including the Omicron variant, two‐tube multiplex qRT‐PCR can detect five copies of viral RNA 58 . Next‐generation sequencing has become the gold standard for identifying Omicron.…”
Section: Detection Of Omicron Variantmentioning
confidence: 99%